COVID-19 -AFFECTING MALNUTRITION IN INDIA - Kanchan Sandhu (International Journal of Organizational Business Excellence, 2020)
Covid-19 has posed bizarre challenges for all over the world including India. Though the number of patients suffering with Covid-19 is small compared to many other countries, still the Covid-19 has smacked the already going on scuffle with unemployment and malnutrition in India. The human race slept in a different world and woke up in a world affected and fearedwith Covid-19. No one was prepared for such a pandemic. The hasty multiplication of corona virus affected patients changed the world massively. Bythe time its horrific effect is realized, it has already spread world over. Though, theeffect of Covid -19 is not time bound or geographically limited but its impact on mankind, livelihoods, health and mindsets is going to be everlasting.